STUDI FENOMENOLOGI POST PARTUM DEPRESION (PPD) PADA IBU NIFAS DENGAN KOMPLIKASI COVID-19 - Rusfita Retna; Reni Sumanti (Jurnal Ilmiah Medsains, 2022)
Postpartum depression (PPD) is a serious family mental health problem in the long term and isrelated to the issue of mother-child safety. Some mothers during the puerperium managed to adjustwell, but some others were less able to handle it so they were prone to experiencing psychologicaldisorders, namely Post Partum Depression. Postpartum depression is a continuation of the baby bluesthat is not managed properly. The research method used in this study is a qualitative narrative method.The population is all postpartum mothers. The sample in this study were postpartum mothers at theBanjarnegara Health Center in a certain period of time. Data analysis using coding and datatriangulation. Based on a qualitative analysis of the phenomenological events of post partumdepression with a history of reactive covid, several themes were found, namely maternal knowledgeabout covid, changes in postpartum physiology, psychological changes during the postpartum periodand family support. It is necessary to do basic psychological screening in postpartum care to preventPost Partum Depression in the puerperium and increase knowledge about the management andrecognition of signs and symptoms of postpartum depression in postpartum mothers.